ENTREPRENEURSHIP EDUCATION AND BUSINESS OPPORTUNITY EXPLOITATION: POSITIVE EMOTION AS MEDIATOR - Othman, Nor Hafiza; Othman, Norasmah; Juhdi, Noor Hasni (Jurnal Cakrawala Pendidikan, 2020)
Entrepreneurship education can facilitate students’ competency development and enhance their self-employment potential. Students’ involvement in entrepreneurship is influenced by their emotions, especially in the early stages of business start-ups. Without exploiting potential business opportunities, entrepreneurship will not occur. This study aims to determine positive emotion effects on the relationship between entrepreneurship education and business opportunity exploitation. The study’s sample comprise of 152 final year university students. A questionnaire-based survey was the main instrument employed and the hypotheses developed were tested using Partial Least Squares-Structural Equation Modeling. The findings show that the students’ action to exploit opportunities is significant, and is affected by the exposure to entrepreneurial learning and anticipated effect of positive emotion on entrepreneurship. This finding confirms that anticipated positive emotions are important throughout the entrepreneurial process and form a motivating factor to engage in entrepreneurial activities. Furthermore, the result shows that positive emotions partially mediate the relationship between entrepreneurship education and opportunity exploitation. This study is important for students to experience a paradigm shift towards entrepreneurship and to encourage them to select entrepreneurship as a career option. Future studies could explore the effect of anticipated negative emotions among tertiary education students, and potential entrepreneurs.